2008
DOI: 10.1592/phco.28.9.1194
|View full text |Cite
|
Sign up to set email alerts
|

Development of Unilateral Cervical and Supraclavicular Lymphadenopathy After Human Papilloma Virus Vaccination

Abstract: A 26-year-old woman developed significant unilateral anterior cervical and supraclavicular lymphadenopathy 3 days after receiving her first dose (of a total of three doses) of human papilloma virus (HPV) vaccine. She had no history of lymphadenopathy after other previous immunizations, and had received no vaccines other than HPV at that time. The left-sided lymphadenopathy developed after she was vaccinated in the left deltoid muscle. The spatial and temporal relationships between the appearance of the lymphad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 8 publications
0
43
1
2
Order By: Relevance
“…We reviewed the current literature and found a single case report of lymphadenopathy after HPV vaccination, described in a 26-year-old woman. We did not find any reports of post-HPV 9-valent vaccination lymphadenopathy in children 12…”
Section: Introductioncontrasting
confidence: 70%
“…We reviewed the current literature and found a single case report of lymphadenopathy after HPV vaccination, described in a 26-year-old woman. We did not find any reports of post-HPV 9-valent vaccination lymphadenopathy in children 12…”
Section: Introductioncontrasting
confidence: 70%
“…Lymphadenopathy of the arm and neck was among the unsolicited side effects in the FDA's report with 64 cases; however, it should have been a predictable side effect due to it being common with other vaccines such as the human papillomavirus vaccine and influenza vaccine [35][36][37] Therefore, in this study, lymphadenopathy was among the general side effects of the COVID-19 vaccine and its overall prevalence was 16.2%, with a higher frequency among females compared to males (16.8% vs. 10.6%), young adults compared to old adults (17.3% vs. 15.1%), and people with allergies (21.4% vs. 14.5%), asthma (17.6% vs. 14.1%), bowel disease (25% vs. 14.3%), cardiac disease (25% vs. 14.2%), COPD (20% vs. 14.8%), DM type-2 (19% vs. 14.5%), and neurologic disease (30% vs. 14.2%). The majority of participants with lymphadenopathy reported that its duration was either one day (18.9%), three days (43.9%), or five days (18.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Based on former experiences, H1N1 Influenza, smallpox, measles, Bacille Calmette-Guerin, and human papillomavirus (HPV) vaccines can cause infrequent axillary LAP ( 27 , 28 , 29 , 30 , 31 ). Several studies showed increased axillary nodal FDG uptakes following H1N1 influenza vaccination in the FDG PET/CT imaging.…”
Section: Discussionmentioning
confidence: 99%